Influence of Chlorhexidine and Prontosan on Dual Species and Monospecies Biofilms Formed by Staphylococcus aureus and Pseudomonas aeruginosa - M. V. Kuznetsova; Yu. A. Encheva; V. A. Samartsev (Антибиотики и Химиотерапия)
The effect of two antiseptics, i. e. chlorhexidine bigluconate 0.5% solution and Prontosan® on dual species and monospecies biofilms formed in vitro by the reference strains P.aeruginosa ATCC®27853 and S.aureus ATCC®29213 was examined. It was demonstrated by atomic force microscopy that under the biocide action there occurred phenotype changes of the structural organization of the bacterial biofilms and morphology of the sessile cells: the cocci were lesser in diameter and the rods were reduced. A reliable change of linear cell sizes was accompanied by increase of their roughness (Sq) that was more pronounced for Prontosan®. When assessing the cell viability it was found that Prontosan® inhibited the bacterial viability in mixed and monospecies biofilms formed on both hydrophilic and hydrophobic abiotic surfaces. In the latter case the biofilm biomass (determined by crystal violet assay) lowered in all the variants of the experiment.